Speech Functions by the Main Character in Wonder Movie in Teaching Speaking - Galuh Kirana Wijayanti; Zulia Chasanah (Department of English Language Education, Universitas Muhammadiyah Purworejo, Indonesia, 2021)
The aims of this study are to identify the types of speech function used by the main character in Wonder movie and to describe the application of speech function found for teaching speaking. The study is designed as descriptive qualitative. The instrument of the study was the researcher. In collecting data, the researcher used audio-visual material and document analysis. The researcher used inductive type to analyze the data. The result shows that there are 289 utterances used by the main character in Wonder movie classified into six types of speech function. Those are 64 (22%) expressive, 24 (8%) directive, 167 (58%) referential, 7 (3%) metalinguistic, 9 (3%) poetic, and 18 (6%) phatic. Based on the result, the kinds of speech function used by main character in Wonder movie can be applied in teaching speaking at the eleventh grade of senior high school.